Association of circulating neuregulin 4 with metabolic syndrome in obese adults: a cross-sectional study. Issue 1 (December 2016) - Cai, Chengfu; Lin, Mingzhu; Xu, Yanfang; Li, Xuejun; Yang, Shuyu; Zhang, Huijie
Abstract Background Neuregulin 4 (Nrg4) is a secreted adipokine recently identified as playing an important role in modulating systemic energy metabolism and the development of obesity-associated disorders. However, information is not available regarding the association between circulating Nrg4 and risk of metabolic syndrome (MetS) in humans. Methods We measured serum Nrg4 in 1212 obese adult subjects (aged 40 years or older), with a waist circumference greater than 90 cm for men or 80 cm for women, recruited from the community. Results MetS subjects had lower levels of circulating Nrg4 than healthy controls (P  < 0.01). The prevalence of MetS was higher in subjects with lower levels of circulating Nrg4 compared to those with higher values (67.3 % vs. 57.4 %, P  < 0.05). Likewise, subjects with low levels of circulating Nrg4 had high prevalence of raised fasting glucose and blood pressure, but there was no association with raised triglycerides and reduced HDL-c. In multivariable logistic regression analyses, increased serum Nrg4 was significantly associated with reduced risk of MetS (OR: 0.603; 95 % CI, 0.439–0.828;P  = 0.002), adjusting for age, gender, current smoking, alcohol consumption, physical activity, BMI, systolic blood pressure, fasting glucose, triglyceride, HDL-c, HOMA-IR, and body fat mass; however, such associations with serum Nrg4 were not noted for each component of MetS. Conclusions These findings indicate that circulating Nrg4 concentrations are inversely associated with risk of MetS in obese Chinese adults, suggesting that circulating Nrg4 concentrations may be a protective factor in the development of MetS.